2016
DOI: 10.1080/19312458.2016.1150444
|View full text |Cite
|
Sign up to set email alerts
|

Manipulated vs. Measured: Using an Experimental Benchmark to Investigate the Performance of Self-Reported Media Exposure

Abstract: Media exposure is one of the most important concepts in the social sciences, and yet scholars have struggled with how to operationalize it for decades. Some researchers have focused on the effects of variously worded self-report measures. Others advocate the use of aggregate and/or behavioral data that does not rely on a person's ability to accurately recall exposure. The present study introduces the prototype of an experimental design that can be used to improve measures of exposure. In particular, we show ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Instead, we found that self-reported accuracy was statistically similar regardless of whether or not farmers received detailed information about how their data would be used for satellite yield estimation and about potential study benefits. These findings support a previous study where authors did not find a significant difference in the accuracy of self-reported responses when study design explanations were framed differently (Jerit et al, 2016). It is important to note, however, that our intervention was limited.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, we found that self-reported accuracy was statistically similar regardless of whether or not farmers received detailed information about how their data would be used for satellite yield estimation and about potential study benefits. These findings support a previous study where authors did not find a significant difference in the accuracy of self-reported responses when study design explanations were framed differently (Jerit et al, 2016). It is important to note, however, that our intervention was limited.…”
Section: Discussionsupporting
confidence: 90%
“…As digital media platforms become central to the mass media landscape, health communication campaigns are increasingly using these digital platforms to efficiently deliver messages to their target audience. Given the challenges associated with objectively measuring exposure to digital content, such as restrictions put in place by social media companies and users' concerns about privacy, researchers continue to rely on self-reported measures to estimate exposure to ad campaigns [34]. Our results indicate that self-reported ad recall provides a meaningful measure of exposure to public health messages delivered on digital platforms.…”
Section: Discussionmentioning
confidence: 83%
“…If available, population averages can provide useful cues for respondents to accurately estimate the frequency of their own behavior (Burton & Blair, 1991;Prior, 2009a;Schwarz & Oyserman, 2001). Alternatively, cues on individual situations of media use might improve response accuracy (Jerit et al, 2016;Potts & Seger, 2013). The internet is typically used at scattered moments throughout the day and oftentimes for incidental aims, such as checking e-mails or the news.…”
Section: Factors Influencing Response Accuracymentioning
confidence: 99%
“…Second, the use of anchor questions that primed the individual context of internet use (Jerit et al, 2016;Potts & Seger, 2013) was tested with an experimental design. Triggering respondents to think about their previous day and week was not found to facilitate more accurate estimations and reports.…”
Section: No Differencesmentioning
confidence: 99%